Chromosomal abnormality variation detected by G‐banding is associated with prognosis of diffuse large B‐cell lymphoma treated by R‐CHOP‐based therapy. (23rd February 2018) - Mizuno, Yoshimi; Tsukamoto, Taku; Kawata, Eri; Uoshima, Nobuhiko; Uchiyama, Hitoji; Yokota, Isao; Maegawa, Saori; Takimoto, Tomoko; Tanba, Kazuna; Matsumura‐Kimoto, Yayoi; Kuwahara‐Ota, Saeko; Fujibayashi, Yuto; et al.
Abstract: Diffuse large B‐cell lymphoma (DLBCL), which is the most prevalent disease subtype of non‐Hodgkin lymphoma, is highly heterogeneous in terms of cytogenetic and molecular features. This study retrospectively investigated the clinical impact of G‐banding‐defined chromosomal abnormality on treatment outcomes of DLBCL in the era of rituximab‐containing immunochemotherapy. Of 181 patients who were diagnosed with DLBCL and treated with R‐CHOP or an R‐CHOP‐like regimen between January 2006 and April 2014, metaphase spreads were evaluable for G‐banding in 120. In these 120 patients, 40 were found to harbor a single chromosomal aberration type; 63 showed chromosomal abnormality variations (CAVs), which are defined by the presence of different types of chromosomal abnormalities in G‐banding, including 19 with two CAVs and 44 with ≥3 CAVs; and 17 had normal karyotypes. No specific chromosomal break point or numerical abnormality was associated with overall survival (OS) or progression‐free survival (PFS), but the presence of ≥3 CAVs was significantly associated with inferior OS rates (hazard ratio (HR): 2.222, 95% confidence interval (CI): 1.056–4.677, P = 0.031) and tended to be associated with shorter PFS (HR: 1.796, 95% CI: 0.965–3.344, P = 0.061). In addition, ≥3 CAVs more frequently accumulated in high‐risk patients, as defined by several conventional prognostic indices, such as the revised International Prognostic Index. In conclusion, our results suggest that the emergence of more CAVs, especially ≥3, based on chromosomal instability underlies the development of high‐risk disease features and a poor prognosis in DLBCL. Abstract : The existence of more chromosomal abnormality variations associates with poor prognosis in diffuse large B‐cell lymphoma, indicating the negative prognostic impact of karyotypic evolution.